2020
DOI: 10.2196/18961
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Interest and Telehealth Capacity of US Hospitals in Response to COVID-19: Cross-Sectional Analysis of Google Search and National Hospital Survey Data

Abstract: Background As the novel coronavirus disease (COVID-19) is widely spreading across the United States, there is a concern about the overloading of the nation’s health care capacity. The expansion of telehealth services is expected to deliver timely care for the initial screening of symptomatic patients while minimizing exposure in health care facilities, to protect health care providers and other patients. However, it is currently unknown whether US hospitals have the telehealth capacity to meet the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 9 publications
1
176
0
6
Order By: Relevance
“…Recently, UW Medicine shared their recommendations of tele-ICU to support rapid preparation for the COVID-19 crisis by integrating a teleconferencing tool, documentation templates, dashboard metrics, and EMR data [196]. Hong et al called for increased investment in facilitating tele-ICU infrastructures, as the current capacity of tele-ICU does not meet the established demand of patients in the United States during the pandemic [197]. To achieve reliable and realtime connectivity, care standardization, patient comfort, staff safety and clinical decision support, innovative technologies, such as Internet of Medical Thing, 5G, AI and various autonomous monitoring and regulation techniques, are expected to strengthen the benefits of tele-ICU and help future scaling up.…”
Section: B Tele-icumentioning
confidence: 99%
“…Recently, UW Medicine shared their recommendations of tele-ICU to support rapid preparation for the COVID-19 crisis by integrating a teleconferencing tool, documentation templates, dashboard metrics, and EMR data [196]. Hong et al called for increased investment in facilitating tele-ICU infrastructures, as the current capacity of tele-ICU does not meet the established demand of patients in the United States during the pandemic [197]. To achieve reliable and realtime connectivity, care standardization, patient comfort, staff safety and clinical decision support, innovative technologies, such as Internet of Medical Thing, 5G, AI and various autonomous monitoring and regulation techniques, are expected to strengthen the benefits of tele-ICU and help future scaling up.…”
Section: B Tele-icumentioning
confidence: 99%
“…As secondary transmissions have occurred and the speed of transmission is accelerating, there are rising concerns about community infections and the overwhelming majority of cities have launched higher level response [6,7]. The current prevention and control about the situation are grim.…”
Section: Introductionmentioning
confidence: 99%
“…20 It is very likely that patients will be willing to engage with teleconsultation when face-to-face access to health care is restricted. Using internet search volume data from Google Trends, Hong et al 21 showed that the U.S. population's interest in telehealth increased as the number of COVID-19 cases increased, with a strong correlation between population interest and COVID-19 cases reported (r = .948, P < .001).…”
Section: Discussionmentioning
confidence: 99%